Nanoparticles as Versatile Tools for Mechanotransduction in Tissues and Organoids - Abdel Fattah, Abdel Rahman; Ranga, Adrian (Frontiers in Bioengineering and Biotechnology, 2020)
Organoids are 3D multicellular constructs that rely on self-organized cell differentiation, patterning and morphogenesis to recapitulate key features of the form and function of tissues and organs of interest. Dynamic changes in these systems are orchestrated by biochemical and mechanical microenvironments, which can be engineered and manipulated to probe their role in developmental and disease mechanisms. In particular, the in vitro investigation of mechanical cues has been the focus of recent research, where mechanical manipulations imparting local as well as large-scale mechanical stresses aim to mimic in vivo tissue deformations which occur through proliferation, folding, invagination, and elongation. However, current in vitro approaches largely impose homogeneous mechanical changes via a host matrix and lack the required positional and directional specificity to mimic the diversity of in vivo scenarios. Thus, while organoids exhibit limited aspects of in vivo morphogenetic events, how local forces are coordinated to enable large-scale tissue architecture changes remains a difficult question to address using current techniques. Nanoparticles, through their efficient internalization by cells and dispersion through extracellular matrices, have the ability to provide local or global, as well as passive or active modulation of mechanical stresses on organoids and tissues. In this review, we explore how nanoparticles can be used to manipulate matrix and tissue mechanics, and highlight their potential as tools for fate regulation through mechanotransduction in multicellular model systems.